(3GdCdajI GdhQOjIs - (3GdhQOj GdeUQj GdcfOj, CHh MaU, GHf GdhQOj, Rjf GdOjf, YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, (B749 (3g`s
(3ChdgG (B:s
(3HGH aj HfGJ GdeGA haQOI GdCSeGc CJi MSfI hddSec GdcHGQ fYei Hjfg (B,, (3haj cHjQg GdZfi Yf bdI cPG GdUZGQ hGdcHGQ LedI s
(3BNQgG (B:s
(3MQa GdjGA jYbhH bGdhG GdeSdejf fYeI hbhI XGgQI hQMeI hGdjOGf JZSd hJbWY GdHGS hbjd JWgjQ ef (B... (3fGS hKjd JhHI hMSf fjI hJeJ GdCdajI GdhQOjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5/67s
(3cTa GdXfhf (B1/157s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3JYHjQ GdQDjGs